DINAMIKA KELEMBAGAAN HUBUNGAN KETENAGAKERJAAN DI MASYARAKAT PERDESAAN (Forum Penelitian Agro Ekonomi, 2017)
In some rural areas, autonomous-formed traditional institutions keep its important roles and well-functioned. Community participation, mainly those who belong to poor group, was quite high both in institutional participation and in decision making process. The reason was that they gained some benefits, both economic and social benefits. The existing institution was adequately dynamic towards internal as well as external factors. Some of these factors could strengthen the institutions, but some others could even destroy the existing institutions. Some factors that contribute strengths to employment relations are (a) those naturally established and formed their own community, (b) selection of members appeared to have been  processed naturally, (c) facing common problems and needs, (d) obey the agreed rules of the games, (e) use simple organizational structure, and (f)  and employ fairness principles.